Do SCFA have a role in appetite regulation? - Darzi, Julia; Frost, Gary S.; Robertson, M. Denise (Proceedings of the Nutrition Society, 2011)
The recently discovered SCFA-activated G-coupled protein receptors FFA receptor 2 and FFA receptor 3 are co-localised in l-cells with the anorexigenic ‘ileal brake’ gut hormone peptide YY, and also in adipocytes, with activation stimulating leptin release. Thus, SCFA such as acetate and propionate show promise as a candidate to increase satiety-enhancing properties of food. We therefore postulate SCFA may have a role in appetite regulation and energy homeostasis. SCFA can be delivered either directly within food, or indirectly via the colon by the provision of fermentable non-digestible carbohydrates. A review of studies investigating the effects of oral SCFA ingestion on appetite suggests that while oral SCFA ingestion is associated with enhanced satiety, this may be explained by product palatability rather than a physiological effect of SCFA. Colon-derived SCFA generated during microfloral fermentation have also been suggested to explain satiety-enhancing properties of non-digestible carbohydrates. However, findings are mixed from investigations into the effects of the prebiotic inulin-type fructans on appetite. Overall, data presented in this review do not support a role for SCFA in appetite regulation.